On the Significance of the Graphic Novel to Contemporary Literary Studies: A Review of The Cambridge Companion to the Graphic Novel: The Cambridge Companion to the Graphic Novel. Stephen Tabachnick (ed.), Cambridge University Press, 2017, ISBN: 9781107519718. Online ISBN: 9781316258316 DOI: https://doi.org/10.1017/9781316258316. Issue 1 (19th September 2018) - Murel, Jacob
Abstract : Stephen Tabachnick's edited collection The Cambridge Companion to the Graphic Novel (2017 ) is reviewed in light of the graphic novel's relevance for contemporary literary studies. This review gives a special focus to the terminological debate surrounding the term 'graphic novel' and what that debate can mean for the field of literary studies as a whole.